Messenger RNA deadenylylation precedes decapping in mammalian cells - Couttet, P. (The National Academy of Sciences of the USA, 1997)
In yeast, the major mRNA degradation pathway is initiated by poly(A) tail shortening that triggers mRNA decapping. The mRNA is then degraded by 5′-to-3′ exonucleolysis. In mammalian cells, even though poly(A) tail shortening also precedes mRNA degradation, the degradation pathway has not been elucidated. We have used a reverse transcription–PCR approach that relies on mRNA circularization to measure the poly(A) tail length of four mammalian mRNAs. This approach allows for the simultaneous analysis of the 5′ and 3′ ends of the same mRNA molecule. For all four mRNAs analyzed, this strategy permitted us to demonstrate the existence of small amounts of decapped mRNA species which have a shorter poly(A) tail than their capped counterparts. Kinetic analysis of one of these mRNAs indicates that the decapped species with a short poly(A) tail are mRNA degradation products. Therefore, our results indicate that decapping is preceded by a shortening of the poly(A) tail in mammalian cells, as it is in yeast, suggesting that this mRNA degradation pathway is conserved throughout eukaryotic evolution.